Fundamentals of electric aircraft - Thalin, Pascal; Thalin, Pascal; Rajamani, Ravi; Maré, Jean-Charles; Taubert, Sven (SAE International, 2023)
"Fundamentals of Electric Aircraft, Second Edition was developed to explain what the electric aircraft stands for by offering an objective view of what can be expected from the giant strides in innovative architectures and technologies enabling aircraft electrification. This edition features new illustrations and photographs throughout. Through tangible case studies, a deep insight is provided into this paradigm shift cutting across various aircraft segments from General Aviation to Large Aircraft. Addressing design constraints and timelines foreseen to reach acceptable performance and maturity levels, Fundamentals of Electric Aircraft, Second Edition puts forward a general view of the progress made to date and what to expect in the years to come. Drawing from the expertise of four industry veterans, Pascal Thalin (editor/contributor), Ravi Rajamani, Jean-Charles Maré, and Sven Taubert (contributors), it addresses futuristic approaches but does not depart too far from the operational down-to-earth realities of everyday business. Fundamentals of Electric Aircraft, Second Edition also offers analyses on how performance enhancements and fuel burn savings may bring more value for money as long as new electric technologies deliver on their promises."--